2008
DOI: 10.1136/bmj.a1379
|View full text |Cite
|
Sign up to set email alerts
|

Misperceptions and misuse of Bear Brand coffee creamer as infant food: national cross sectional survey of consumers and paediatricians in Laos

Abstract: Objective To investigate the use of Bear Brand coffee creamer as a food for infants and the impact on consumers of the logo of a cartoon baby bear held by its mother in the breastfeeding position.Design Interviews with paediatricians throughout the country and a national survey of potential consumers regarding their perceptions and use of the Bear Brand coffee creamer.Setting 84 randomised villages in south, central, and northern Laos.Participants 26 Lao paediatricians and 1098 adults in households in a cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
0
26
1
Order By: Relevance
“…illustrates a billboard in Asia in violation of the Code. This type of widespread marketing results in mothers' recognising certain brands and believing their children will be healthier with formula 26 27…”
Section: Violations Of the Codementioning
confidence: 99%
“…illustrates a billboard in Asia in violation of the Code. This type of widespread marketing results in mothers' recognising certain brands and believing their children will be healthier with formula 26 27…”
Section: Violations Of the Codementioning
confidence: 99%
“…12, 14,18,19 As with the tobacco and alcohol industries, formula companies indulge in practices abroad that may be banned or severely restricted in their home countries. 6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Code violations include promotion of formula products to the public, even in health care facilities.…”
Section: Characteristics Of Code Violations In Low-and Middle-income mentioning
confidence: 99%
“…Only after the BMJ publication of a national survey and a series of rapid responses, which showed that misleading advertising had severe consequences of malnutrition and death, did Nestlé agree to change its logo. 6,18,[20][21][22] After we provided further evidence of deaths in ethnic minority villages, the sale of Bear Brand coffee creamer was discontinued. 25 However, the label reappeared on breast milk substitutes (BMS) and advance formula, advertised for feeding toddlers older than 1 year, but in modified versions: a mother bear holding its cub on its lap but not in the breastfeeding position, or holding a glass of milk instead.…”
Section: Interventions and Their Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems associated with the widespread marketing of formula milk, which is a particular problem in the South, have been recently highlighted 17 18. This widespread marketing of formula milk is effective in reducing the number of women who breast feed.…”
mentioning
confidence: 99%